2021
DOI: 10.1002/oby.23187
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and cognitive impairment

Abstract: Bariatric surgery has been shown to improve cognition in patients with severe obesity. Bariatric surgery may improve mental function in patient populations with obesity and with cognitive impairment, including nonacquired, dementia, and traumatic brain injury, although studies have been limited. Bariatric surgery provides an opportunity to explore the effects of obesity, type 2 diabetes, dyslipidemias, and other expressions of metabolic syndrome on cognition. It offers the unusual opportunity to study patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Some of the positive and negative effects of bariatric surgery were observed also in lean rodents, suggesting that the metabolic and endocrine state induced by surgery can have beneficial or detrimental physiolgoical effects ( Li et al, 2019 ; Ben-Haroush Schyr et al, 2021 ; Akalestou et al, 2022a ; Hefetz et al, 2022 ). Obesity is associated with cognitive decline and is a risk factor for AD ( Ahlskog et al, 2011 ; Ngandu et al, 2015 ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Stephen et al, 2017 ), and bariatric surgery was shown in most studies to improve cognitive function in patients with obesity ( Miller et al, 2013 ; Alosco et al, 2014a , b ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Thiara et al, 2017 ; Prehn et al, 2020 ; Morledge and Pories, 2021 ). This result can have two, non-mutually exclusive explanations: First, weight loss and improvement in metabolic parameters that are affected directly by obesity such as glycemia can reverse or delay cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the positive and negative effects of bariatric surgery were observed also in lean rodents, suggesting that the metabolic and endocrine state induced by surgery can have beneficial or detrimental physiolgoical effects ( Li et al, 2019 ; Ben-Haroush Schyr et al, 2021 ; Akalestou et al, 2022a ; Hefetz et al, 2022 ). Obesity is associated with cognitive decline and is a risk factor for AD ( Ahlskog et al, 2011 ; Ngandu et al, 2015 ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Stephen et al, 2017 ), and bariatric surgery was shown in most studies to improve cognitive function in patients with obesity ( Miller et al, 2013 ; Alosco et al, 2014a , b ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Thiara et al, 2017 ; Prehn et al, 2020 ; Morledge and Pories, 2021 ). This result can have two, non-mutually exclusive explanations: First, weight loss and improvement in metabolic parameters that are affected directly by obesity such as glycemia can reverse or delay cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery has been shown to extend lifespan, improve cognitive function, and enhance quality of life [7,[20][21][22][23]. While there is consensus that surgery should be considered in patients younger than 50 years of age, the European Association for the Study of Obesity eliminates this age limit and encourages select elderly people to consider such operations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery can ameliorate hyperglycemia ( 8 ) and reduce the body weight ( 9 ). In addition, patients underwent such type of surgery showed significant improvement in the cognitive function ( 10 ).…”
Section: Introductionmentioning
confidence: 99%